The IbPYL8-IbbHLH66-IbbHLH118 complex mediates the abscisic acid-dependent drought response in sweet potato - Xue, Luyao (The New phytologist, 2022)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.